Analisis Pengendalian Kerusakan Kantong Pada Proses Pengantongan Pupuk ZA Plus dengan Metode SPC dan FMEA di PT. X - Muhammad Rofi'ul Ichsan; Moh. Jufriyanto; Akhmad Wasiur Rizqi (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. X is a subsidiary of a state-owned enterprise (BUMN), the most complete producer of fertilizers and chemicals in Indonesia. In addition to being engaged in services and logistics, PT X also produces and services bagging services for ZA Plus Fertilizer. The purpose of this research is to analyze the causes of bag defects in the ZA Plus fertilizer bagging process and determine the causes through the application of effective quality control using SPC and FMEA methods. The result of the SPC analysis is that there is still bag defect data that is out of control. While the results of the FMEA method analysis found that the most critical cause of defects is the frequent slip of the sewing needle, with an RPN value of 450. To overcome this problem, this study proposes to replace sewing machine equipment that is worn out regularly and on a scheduled basis.